International Conference on Nutrition & Food Science (ICNFS 2010) Paris, France 28-30 Julai 2010 - Wan Rosli, Wan Ishak (Pusat Pengajian Sains Perubatan, 2010)
Abslract-The proximate composition, physical traits and sensory properties of beef and chicken patties incorporated with various level of dried cornsilk. (MaydiJ stigma) were studied. The beef and ci:J,icken patties were formulated with either 2o/., 4% or 6% of cornsitk. Both cooked beef and chicken patties incorporated with 6% comsilk recorded the highest protein concenttation at 23.3% and 28.42o/o, respectively. Both cooked beef and chicken patties containing 6o/. cornsilk siiruficantly recorded the lowest coDCenlrati.on of fat at ll.4% and 14.60%, respectively. Beef and chicken patties formulated with 6% cornsilk recorded the highest cooking yieJd at 80.13% and 83.03o/. compam:l to other treatments. The inclusion of cornsilk did not change the sensory properties and consumer acceptability of comsilk-ba.sed beef and chicken patties. Cornsilk fibre bali been effective in improving . cooking yield, moisture and fat retention of beef and chicken patties